2021
DOI: 10.1159/000517514
|View full text |Cite
|
Sign up to set email alerts
|

Association between Vitamin D Level and Acne, and Correlation with Disease Severity: A Meta-Analysis

Abstract: <b><i>Background:</i></b> Vitamin D deficiency is frequently associated with several medical conditions. However, a comprehensive meta-analysis assessing the association between vitamin D level and acne is lacking. <b><i>Objective:</i></b> To determine the relationship between vitamin D level and acne, and to assess the association between vitamin D level and acne severity. <b><i>Methods:</i></b> This meta-analysis was assessed by using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…21 Similar findings were reported in a case-control study by Hasamoh et al, who found no significant association between vitamin D levels and the severity of acne vulgaris, which was conducted in Saudi Arabia. 22 In contrast to our finding a systemic review included 10 studies found that all studies (8 of 10) revealed lower serum 25-hydroxy vitamin D levels as the acne severity progresses, although 2 of them were not statistically significant. 23 A small sample size case control study (33 cases and 25 controls receiving vitamin D supplement) in Iraq found that vitamin D deficiency was more frequent in patients with acne, which was inversely related with disease severity, however patient in control group had receive vitamin D supplementation.…”
Section: Discussioncontrasting
confidence: 89%
“…21 Similar findings were reported in a case-control study by Hasamoh et al, who found no significant association between vitamin D levels and the severity of acne vulgaris, which was conducted in Saudi Arabia. 22 In contrast to our finding a systemic review included 10 studies found that all studies (8 of 10) revealed lower serum 25-hydroxy vitamin D levels as the acne severity progresses, although 2 of them were not statistically significant. 23 A small sample size case control study (33 cases and 25 controls receiving vitamin D supplement) in Iraq found that vitamin D deficiency was more frequent in patients with acne, which was inversely related with disease severity, however patient in control group had receive vitamin D supplementation.…”
Section: Discussioncontrasting
confidence: 89%
“…33 Vitamin D deficiency was also associated with acne severity and might involve in acne pathogenesis. 34 In the current study, UV at 305 and 310 nm only showed beneficial effects under relatively low levels of exposure (sun exposure time <1 h/day). UV's immunomodulatory effects also exhibits a dose-dependent manner.…”
Section: Overall and Interactive Effects Of Low Levels Of Uv Exposurementioning
confidence: 49%
“…Besides, UVB radiation induces the synthesis of 1,25(OH) 2 D 3 to reduce the ability of dendritic cells to secret proinflammatory cytokines 33 . Vitamin D deficiency was also associated with acne severity and might involve in acne pathogenesis 34 …”
Section: Discussionmentioning
confidence: 99%
“…9 The vitamin D receptor is found in many organs of the body, including the gastrointestinal tract, immune cells, brain, and skin. 10 Many skin diseases, including lupus erythematosus, atopic dermatitis, hidradenitis suppurativa, acne, alopecia areata, and skin cancer, have been linked to vitamin D. 11 A recent meta-analysis 12 demonstrated significantly low vitamin D levels in patients with acne. There is also some evidence of an inverse association between acne severity and vitamin D levels.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis 12 demonstrated significantly low vitamin D levels in patients with acne. There is also some evidence of an inverse association between acne severity and vitamin D levels.…”
Section: Introductionmentioning
confidence: 99%